Adaptive Navigation Interface Powered by Evolutionary Algorithm - Filatov, T.; Popov, V.; Sakal, I. (ХНУРЭ, 2011)
A combination of adaptive navigational interface and real time collaborative feedback analysis for documents relevance weighting is proposed as an viable alternative to prevailing ‘telegraphic’ approach in information retrieval systems. Adaptive navigation is provided through a dynamic links panel controlled by an evolutionary algorithm. Documents relevance is initially established with standard information retrieval techniques and is further refined in real time through interaction of users with the system. Introduced concepts of multidimensional Knowledge Map and Weighted Point of Interest allow finding relevant documents and users with common interests through a trivial calculation. Browsing search approach, the ability of the algorithm to adapt navigation to users interests, collaborative refinement and the self-organizing features of the system are the main factors making such architecture effective in various fields where nonstructured knowledge shall be represented to the users.
Keywords: evolutionary; adaptive; navigation; web; collaborative; social; interface; information retrieva; knowledge; document; algorithm; adaptive; text; refinement